Silent Sufferings of People with Disability (PWD) and the Barriers faced by them in Pokhara Metropolitan City - Koirala, Pusparaj (Journal of Development and Social Engineering, 2022)
“Silent Sufferings of People with Disability; Physically Disabled People and the Barriers faced by them in Pokhara Metropolitan City” is mainly focused on the different barriers faced by the physical group of PWD and the impact of barriers in their life. The members from disability organizations of Pokhara Valley; established by PWD themselves were selected for study. The findings are based on the field level investigation, observation and in-depth interviews with the 46 members of PWD of different organizations. Disability prevalence is high in rural areas than in city owing to agricultural and rural lifestyle and youth age is more prone to disability. Most of the people with disability are dependent upon their parents for livelihood. Many of the people with disability leave their study in the middle as the schools are not accessible. They are facing different kind of barriers in their life but these sufferings are silent/unheard. People with disability are mistreated and seen as an object of pity which is attitudinal barrier. People with disability especially wheel chair users find difficult to travel from one place to another as public vehicles do not stop for them where as taxi fare is high. Though the people with disability are provided with disability allowance it is nominal. There are many laws and policies formulated regarding the up- liftmen of people with disability. But it is only limited in speech of leaders and papers of bureaucracy. The effective implementation of existing laws and policies are still necessary.